Improving the Quality of Inpatient Services with Lean Service and Six Sigma Methods at Eshmun Hospital - Cristanto Cristanto; Uni Pratama Pebrina Br Tarigan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Hospitals play an important role in the life of the nation and state, because every country has an obligation to meet all the physical and spiritual health needs of every citizen. The main focus of Eshmun Hospital is the accuracy of doctors in diagnosing diseases, responsive patient care, hospital security, hospital access roads, completeness of facilities, and medicines. The research method used in this research is six sigma, pareto diagram, failure mode effect analysis (FMEA), fishbone diagram, and value stream mapping. The conclusions obtained from this research are after repairs are made to the inpatient service activities of the hospital. Eshmun eats service activities which were originally 15 activities reduced to 11 activities, this can save time in carrying out services. Activities that are non-value add are very detrimental, including: the data collection service process is still done manually, patients are still waiting to receive treatment, there are some doctors who are not professional. The main cause of waste is usually caused by hospitals not keeping up with the times, human resources that are not optimal.